Encouraging Students' Pro-environmental Behaviour: Examining the Interplay Between Student Characteristics and the Situational Strength of Schools. (March 2019) - Runhaar, Piety; Wagenaar, Klaartje; Wesselink, Renate; Runhaar, Hens
The goal of this article is to understand how the pro-environmental behaviour (PEB) of secondary school students can be encouraged. In an exploratory study, we examine to what extent pro-environmental cues—that is, 'situational strength' (Mischel, Psychological Review, 80(4):252, 1973)—were present in schools and whether students in 'stronger' situations reported higher levels of PEB than students in 'weaker' ones. Moreover, we examined relationships between student characteristics—gender, perceived behavioural control (PBC), pro-environmental attitudes (PEA) and intentions (Fishbein & Ajzen, Belief, attitudes, intention, and behavior. An introduction to theory and research . Reading, MA: Addison-Wesley, 1975)—and their PEB. A sequential mixed method was used, utilizing data from three Dutch secondary schools. Survey data covering 179 students showed relationships among students' gender, PEA and intentions, and PEB. Qualitative data—derived from semi-structured interviews with staff members, structured assignments for students and observations—showed differences in situational strength between the schools. Moreover, the data suggest an interplay between student characteristics and situational strength in affecting PEB.